2005
DOI: 10.1097/01.ftd.0000158080.61201.65
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Limited Sampling Strategy to Estimate Area Under the Curve of Tacrolimus in Adult Renal Transplant Patients

Abstract: Limited sampling strategies have been developed to predict full AUCs. The goal of this study was to develop a limited sampling strategy to estimate the AUC of tacrolimus in adult renal transplant patients and to evaluate its predictive performance in an independent patient population. A total of 27 tacrolimus pharmacokinetic profiles were studied. Blood samples were collected before the dose (0) and at 0.5, 1, 2, 4, 6, 8, and 12 hours postdose. The study was divided into 2 phases. In phase 1, the goal was to o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(47 citation statements)
references
References 18 publications
4
43
0
Order By: Relevance
“…Two trials showed that the tacrolimus C 0 correlated poorly with AUC (r 2 ϭ 0.11 and 0.362) and that C 4 was the best single-point correlate of AUC (r 2 ϭ 0.79 and 0.81). Both studies suggested that a two-or three-point limited sampling strategy, both of which incorporated C 4 , would predict AUC better than C 0 levels (63,64). Other studies identified C 2 or C 3 as the best correlates of AUC (65,66).…”
Section: Therapeutic Drug Monitoring Of Tacrolimusmentioning
confidence: 99%
“…Two trials showed that the tacrolimus C 0 correlated poorly with AUC (r 2 ϭ 0.11 and 0.362) and that C 4 was the best single-point correlate of AUC (r 2 ϭ 0.79 and 0.81). Both studies suggested that a two-or three-point limited sampling strategy, both of which incorporated C 4 , would predict AUC better than C 0 levels (63,64). Other studies identified C 2 or C 3 as the best correlates of AUC (65,66).…”
Section: Therapeutic Drug Monitoring Of Tacrolimusmentioning
confidence: 99%
“…Especially in the early post-transplant period, the reliance on only Tac TLs results in over-or underestimation of the current Tac exposure. Otherwise, a full PK profile requires the child to be observed for 12 h Abbreviated AUC monitoring, which overcomes the inconvenience to the patient, has already been introduced and used for adults [9,10], yet, for children, very little literature is available. Therefore, we investigated the correlation of Tac TL and 0-12 h AUC, and the use of limited sampling strategies, in paediatric renal transplant recipients whose condition was stable.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on the t 1/2 and the dosing interval, the current C min can be affected by more or less of the previous doses before steady state was reached. [22][23][24][25], but besides being better than C min , their clinical utility is scarce.…”
Section: Discussionmentioning
confidence: 99%